Evaluation of the Psychometric Properties of the Chinese Internet Gaming Disorder Checklist (C-IGDC) Among Chinese Adolescents - Chen, Juliet Honglei; Su, Xiaoyu; Dang, Le; Wu, Anise M. S. (Frontiers in Psychiatry, 2021)
As the first DSM-5 based, multidimensional screening tool of Internet gaming disorder (IGD) designed for Chinese gamers, the Chinese Internet Gaming Disorder Checklist (C-IGDC) has shown satisfactory psychometric properties among Chinese young adults. Given the high vulnerability to IGD among adolescents, the present study aimed to examine the applicability of C-IGDC to Chinese adolescents to address shortfalls in the existing literature regarding the assessment of adolescent IGD screening. Through a two-stage sampling method in a cross-sectional survey, we obtained a sample of 1,253 Chinese past-year adolescent gamers (43.8% female; Mage = 14.49 years, SDage = 1.60 years) from local junior or senior high schools in Macao, China for data analysis. Our results confirmed a good model fit of the original two-level, nine-subfactor structure of the 27-item C-IGDC, and indicated adequate internal consistency and test–retest reliability, as well as good concurrent validity as evidenced by expected associations with IGD functioning impairments, gameplay characteristics, and depressive symptoms. An optimal screening cutoff score (≥20) was proposed to identify probable disordered gamers among Chinese adolescents with past-year gaming experience. The findings support the extended use of C-IGDC to Chinese adolescents as a reliable and valid assessment tool for evaluating IGD severity levels and screening for probable IGD cases. Its use can facilitate a proper screening procedure for probable IGD cases in both school and clinical settings.